Integration of Spatial and Demographic Data into a Web-Based Platform for the Family Planning Program Using the Closed Polygon Method (A Case Study in Pekalongan City) - Agus Ilyas; Sattriedi Wahyu Binabar; Tri Agus Setiawan; Hari Agung Budijanto (Computing and Information System Journal, 2025)
The Family Planning (FP) program requires a data-driven approach to enhance service effectiveness. This study aims to develop a web-based platform that integrates spatial data (based on closed KML polygons) with demographic data to map the FP program’s target areas in Pekalongan City. The closed polygon method is used to accurately delineate administrative regions (urban villages, community units, or neighborhood units), while demographic data (reproductive age groups, active FP participants, etc.) are dynamically displayed in an interactive interface. The platform is built using Leaflet.js (web mapping) and MySQL (spatial database), enabling density analysis of FP targets per area. Trial results show that this integration increases targeting precision by 25% compared to conventional methods, while also facilitating monitoring by relevant agencies. This study demonstrates that a geospatial approach using closed polygons can be an efficient solution for managing FP programs in urban areas like Pekalongan. The findings show that using closed polygons in FP mapping provides more accurate visualization of population density and service distribution. With the web-based platform, accessibility and monitoring of FP programs can be improved, enabling more effective data-driven decision-making.